2020
DOI: 10.3389/fbioe.2020.00159
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Compressive Forces in Adolescent Idiopathic Scoliosis With and Without Carrying Loads: A Musculoskeletal Modeling Study

Abstract: Frontiers in Bioengineering and Biotechnology | www.frontiersin.org 1 March 2020 | Volume 8 | Article 159 Schmid et al. Spinal Loading in AISforces further increased depending on the carrying mode and the weight of the load. These results can be used as a basis for further studies investigating segmental loading in AIS patients during functional activities. Models can thereby be created using the same approach as proposed in this study.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…Larger deformity provides larger vertebral rotation in the coronal plane at upper and lower end levels of the scoliotic curve (Figure 2E), which results into larger contribution of the transferred load relatively to the lateral axis in the vertebral reference system (Figure 2E, upper right corner). As concerns the activation of MF and ES muscle, the slightly positive values (similar between groups) of the normalized activity ratio indicate a larger activation in the convex side of the scoliotic curve, in agreement with our previous findings (Barba et al, 2021) and with other numerical and experimental studies (Schmid et al, 2020;Cheung et al, 2005;Kwok et al, 2015). Overall, the biomechanical parameters did not provide a priori information about the risk of curve progression.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Larger deformity provides larger vertebral rotation in the coronal plane at upper and lower end levels of the scoliotic curve (Figure 2E), which results into larger contribution of the transferred load relatively to the lateral axis in the vertebral reference system (Figure 2E, upper right corner). As concerns the activation of MF and ES muscle, the slightly positive values (similar between groups) of the normalized activity ratio indicate a larger activation in the convex side of the scoliotic curve, in agreement with our previous findings (Barba et al, 2021) and with other numerical and experimental studies (Schmid et al, 2020;Cheung et al, 2005;Kwok et al, 2015). Overall, the biomechanical parameters did not provide a priori information about the risk of curve progression.…”
Section: Discussionsupporting
confidence: 88%
“…At this stage, we thus preferred to limit the simulation to the upright posture, although expected to provide lower spinal loads and muscle activities compared to the motion tasks (Dreischarf et al, 2016). According to that performed in previous similar works (Schmid et al, 2020;Barba et al, 2021), the evaluation of muscle activation as predictor of the scoliosis progression was limited to ES and MF. In this regard, additional groups such as quadratus lumborum, internal obliques, and latissimus dorsi could be considered as potential predictors in future developments simulating the motion of the trunk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmid et al also observed muscle geometry and activity asymmetry. 142 They reported the predicted muscle volume was generally in line with the literature; the majority of the models had larger erector spinae volumes on the convex side of the curve, and one third had larger volumes on the concave side. However, for the multifidi muscles Schmid et al reported larger volumes on the concave side for about 90% of the models.…”
Section: Methodssupporting
confidence: 70%
“…Asymmetric muscle activity partially agreed with the literature, however differences could be attributed to differences between the curvature of the models and the subjects in the literature. 142 Previous studies have also found that the scoliotic spine experienced greater muscle force asymmetry than a healthy spine. 119 …”
Section: Methodsmentioning
confidence: 96%